Islamic values integration in early childhood education: A multi-site case study of curriculum practices in Banjarmasin, Indonesia - Ningtyaz, Dian Kusuma; Aslamiah, Aslamiah; Darmiyati, Darmiyati (Asatiza: Jurnal Pendidikan, 2025)
This study investigates the management of Islamic-integrated curricula within Indonesian early childhood education, focusing on two institutions in Banjarmasin: PAUD IT Ukhuwah and PAUD Tahfidz Ummul Qura. It addresses a limited understanding of how religious values are operationalized through curriculum management. Employing a qualitative case study approach, data were gathered from 11 in-depth interviews with teachers, principals, and parents, supplemented by classroom observations and document analysis. The results demonstrate two distinct pedagogical models. PAUD IT Ukhuwah implements a thematic-integrative model, connecting Quranic verses to weekly themes for holistic learning. PAUD Tahfidz Ummul Qura focuses on a memorization-based approach, incorporating daily tahfidz sessions supported by individualized student coaching. Both institutions facilitate teacher empowerment through structured training and religious mentoring. Furthermore, each employs systematic monitoring and evaluation frameworks that comply with national early childhood education standards. The study highlights the significance of comprehensive curriculum management for nurturing spiritual and moral development in young children. By detailing these context-specific practices, this research contributes to international discussions on faith-based education. It provides practical insights for policymakers and educators, including recommendations to scale effective teacher training models for religious pedagogy, adapt integrative thematic frameworks for value-based education, and develop national guidelines for monitoring and evaluating religious-based ECE programs.